Kant on the Limits of Human Knowledge - Natheif , Aysheh R. (Jordan Journal of Social Sciences, 2022)
This paper tackles Kant’s theory of knowledge. The authors explain Kant’s answer to the questions he put forward, i.e. What can I know? What and how senses and understanding know? And what part of knowledge is a priori? And what is posteriori? To answer these questions, Kant wrote his great book ‘Critique of Pure Reason’ on which the authors depend in this paper. The main idea Kant start with is “though all our knowledge begins with experience, it does not follow that it all arises out of experience”. In Kant’s view, knowledge arises from the combination of sense intuitions which are the manifold of representations of things as they appear to us, with the pure concepts of the understanding, i.e., categories, under what Kant called “the synthetic unity of apperception” i.e., the “I think” which must accompany all our representations. Kant used the faculty of imagination which creates schemata to facilitate the employment of the pure concepts of the understanding, i.e., categories to the manifold of sense intuitions. The authors concluded with Kant that our knowledge is limited to the scope of experience.